Perencanaan Kebutuhan Alat Gali-Muat dan Alat Angkut Batukapur di Area Pit Limit pada Tambang Quarry PT. Semen Padang, Sumatera Barat - Siska Rahayu; Murad Murad (Departemen Teknik Pertambangan FT UNP, 2020)
Abstract. PT. Semen Padang is one of the companies engaged in mining, especially limestone, silica, clay and iron. Which mining is located in Batu Karang Putih Bukit Ngalau, Indarung Village, Kuranji District, Padang City, West Sumatra Province. With the opening of mining in the pit limit area with limestone reserves and the many production demands, mining is carried out in the pit limit area. Based on the description above, it is necessary to estimate the number of loading and hauling tools to be used and an estimate of the total operational costs to be incurred in limestone mining for the pit limit area at PT. Semen Padang.The calculation of the results of the need for the equipment obtained using the same tool is using a Komatsu PC 1250 Excavator digging tool and HD 785-7 type Dump Truck. The results in 2019 from September to December were 1 unit of Exca and 2 units of Dump Truck, in 2020 there were 1 unit of excavator and 3 units of dump truck, in 2021 there were 1 exca and 3 units of dump truck. And in 2022 there will be 1 excavator and 2 dump trucks. For operational costs per year on the komatsu PC 1250 excavator unit digging equipment amounting to Rp.1,484,457,648 / Year and operational costs for loading unit HD 785-7 units Rp. 8,627,409,264/years.Keywords: limestone, operating cost, Excavator, Dump Truck, Produksi